Evaluation of three dimensional conformal radiation therapy of oesophageal cancer: a dosimetric study. Issue 3 (5th December 2018) - Zulkafal, Hafiz Muhibb ullah; Iqbal, Muhammad Mazhar; Akhtar, Muhammad Waqas; Iqbal, Khalid; Khan, Muhammad Afzal
Abstract: Aims: The main objective of this research work is to compare the dosimertic effect on lower and upper oesophagus cancer treatment using 3D conformal radiotherapy as well as to evaluate the doses administered to the organs at risk. Materials and methods: In this study, a cohort of 30 oesophageal cancer patients between the ages of 45 and 67 years registered during March 2017 to February 2018 was considered. These patients were treated through 3D conformal radiotherapy using four-field technique. Beam energy of 15 MV from Varian DHX linear accelerator was used. The given 30 patients were divided into two groups. The 1st group of 15 patients with upper oesophagus cancer was prescribed 5000 cGy doses, and the 2nd group of remaining 15 patients with lower oesophagus cancer was prescribed 4500 cGy. Computed tomography scans of every patient were obtained and then transmitted to Eclipse TPS for generating treatment plans. All radiotherapy plans were evaluated through various dosimetric indices. Statistical analysis software SPSS was utilised to get the values of means standard error and standard deviation of these indices for the treatment plan evaluation. Results: Uniformity index (UI) calculated for first group of patients showed difference of 7·4% from ideal value. A difference of 7% between ideal and calculated UI value was observed in 2nd group of patients. The values of other dosimetric indices like coverage, homogeneity, moderate dose homogeneity index (mDHI) and radical dose homogeneity index (rDHI) were found in limits specified by the Radiation Therapy and Oncology Group. The maximum difference of 6% was observed between the coverage mean values of 1 st and 2 nd group treatment plans. Conclusion: For oesophageal cancer, 3D conformal radiotherapy using four-field treatment plans shows homogeneous distribution of dose around the target and limits the dose to organ at risk.